Enhanced adsorptive removal of indigo carmine dye by bismuth oxide doped MgO based adsorbents from aqueous solution: equilibrium, kinetic and computational studies. Issue 38 (31st August 2022) - Adam, Fatima A.; Ghoniem, M. G.; Diawara, Moussa; Rahali, Seyfeddine; Abdulkhair, Babiker Y.; Elamin, M. R.; Ben Aissa, Mohamed Ali; Seydou, Mahamadou
Abstract : The IC adsorption mechanism on the Bi2 O3 doped MgO nanosorbents occurred through the chemisorption process. Abstract : Novel doped MgO nanoadsorbents were effectively fabricated at various Bi2 O3 doping concentrations (0, 2.5, 5 and 10%). DFT-D3 study showed that the doping is done by substitution of two magnesium atoms by two bismuth atoms with the creation of a vacancy of one Mg atom. TEM, SEM, EDX, BET, XRD, and FTIR were used to characterize the obtained nanostructures. The removal of indigo carmine (IC) dyes from wastewater by doped MgO nanoparticles is investigated. Experimental parameters such as the initial dye concentration, contact time, Bi2 O3 doping concentration, and pH were optimized to enhance the adsorption capacity. Bi2 O3 doped MgO prepared at 5% (MgOBi2) is the best adsorbent with a maximum IC adsorption capacity of 126 mg g −1 at a solution pH equal to 7.00 and contact time of 74 min. The results indicated that the adsorption process followed pseudo-second-order (PSO) reaction kinetics, and the Freundlich isotherm model gave a better goodness-of-fit than the linear Langmuir model. The FTIR study established that IC molecules are successfully adsorbed onto the surface of MgOBi2 via a chemisorption process.